1975
DOI: 10.1042/bj1470045
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus oryzae acid proteinase. Purification and properties, and formation of π-chymotrypsin

Abstract: An acid proteinase from Aspergillus oryzae was isolated from a commercial powder by successive (NH4)2SO4 fractionation, acetone precipitation, and ion-exchange chromatography on phosphate- and DEAE-cellulose columns. The purified enzyme was found to be homogeneous by ultracentrifuge-sedimentation analysis (S20, W equal 3.63S), but electrofocusing in polyacrylamide gels and electrophoresis at pH 3.2 revealed that it consists of two very closely migrating bands. No difference in the amino acid composition and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 33 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…It is well documented that A. oryzae secretes proteases, including aminopeptidases, serine endopeptidases, aspartic endopeptidases, etc. 30,31 Sardjono et al 23 demonstrated that protease activity from A. oryzae reached its highest levels after a 48-hour fermentation and had no further increase after a 48-hour fermentation. This suggests that the 48-hour fermentation used in this study provides the most efficient production of small-size peptides, without excessive nutrient use for metabolism.…”
Section: Resultsmentioning
confidence: 97%
“…It is well documented that A. oryzae secretes proteases, including aminopeptidases, serine endopeptidases, aspartic endopeptidases, etc. 30,31 Sardjono et al 23 demonstrated that protease activity from A. oryzae reached its highest levels after a 48-hour fermentation and had no further increase after a 48-hour fermentation. This suggests that the 48-hour fermentation used in this study provides the most efficient production of small-size peptides, without excessive nutrient use for metabolism.…”
Section: Resultsmentioning
confidence: 97%
“…(Figure 6 c). These results suggest that the productive secretions of hydrolytic enzymes, such as proteases [23] from the microorganism during their growth caused the degradation of the gel materials.…”
Section: Fungal Growth On Copoly[orn/orn(cou)] Hydrogelmentioning
confidence: 88%
“…Davidson et al 27 ) and Tujita and End0 28 ) have independently purified acid proteases from commercial enzyme preparations of A. oryzae and have analyzed their amino acid compositions, which correlate well. In addition, the amino acid composition of the mature protein deduced from DNA sequence of the cloned pepA gene is almost identical with those reported (Table I).…”
Section: Discussionmentioning
confidence: 99%